БОЛАЛАРНИ ЭРКАЛОВЧИ ХАЛҚ ҚЎШИҚЛАРИ - Шоймардонов, И. (SCIENCE and SOCIETY, 2020)
The article deals with importance of interpreting children’s Surkhan folk in upbringing spiritual-moral of children by means of childrens games and term which were recorded by Bakshi.